133 Normal pressure hydrocephalus – factors affecting surgical outcomes. Issue 6 (27th May 2022) - Carey, Charles; Inam, Masna; Tsermoulas, Georgios; Flint, Graham; Jacob, Saiju
Abstract : Background: Normal pressure hydrocephalus (NPH) is a disease that causes gait disturbance, urinary incontinence and dementia and is treated through ventriculoperitoneal shunting (VPS). Although CSF infusion studies are currently used to predict the likelihood of improvement following VPS, many see no benefit or deteriorate after initial improvement. It is currently unknown whether preoperative characteristics could predict the likelihood of postoperative improvement. Aims: To investigate associations between postoperative symptomatic improvement and patients' mean baseline and plateau CSF pressures, the time between NPH diagnoses and performing VPS, and patients' age at diagnosis. Methods: A retrospective audit was performed using data collected between 14/05/2018 and 18/06/2018 from 65 NPH patients treated with VPS at University Hospital Birmingham. Percentages of patients whose symptoms improved and did not improve postoperatively were calculated. Two-tailed unpaired t-tests were performed to analyse associations between the pre-operative factors studied and symptomatic improvement. The level of significance used was p = 0.05. Results: 69.0% of patients with gait disturbance, 52.9% with urinary incontinence and 56.4% with cognitive impairment at baseline showed improvement at their first postoperative follow up. Just 31.0% of patients with gait disturbance, 47.1% with urinary incontinence and 43.6% with cognitive impairment showed improvement at their last postoperative follow up. None of the pre-operative factors studied were associated with significant differences in the rates of symptomatic improvement at patients' first or last recorded follow ups. Conclusions: The majority of patients showed improved gait, incontinence, and cognition postoperatively at their first recorded follow up. The mean rates of improvement in all 3 symptoms studied at patients' last recorded follow up were lower than at their first recorded follow up. There were no associations with symptomatic improvement with the number of weeks between diagnosis and VPS, age at diagnosis, baseline CSF pressure and plateau CSF pressure. saiju.jacob@uhb.nhs.uk